Compact, snapshot and triple-wavelength system for ICF target ice-layer refractive index and thickness measurement. (February 2021) - Yan, Tianliang; Wang, Kai; Zang, Zhongming; Lu, An; Hu, Xiaobo; Chen, Nan; Zhang, Huxiang; Liu, Chong; Liu, Dong
Highlights: The snapshot and compact system enables fast in-situ measurement. Three wavelengths are used to study the dispersion characteristic of the layers. The measurement accuracy of the system is better than 2.1%. Abstract: We propose a compact system for testing ICF (inertial confinement fusion) target shell/ice-layer refractive index and thickness simultaneously and in-situ at triple-wavelength. The system is composed of a Mach-Zehnder interference test configuration and a backlit shadowgraph test configuration. With the OPD (optical path difference) and ray deflection information extracted from the two test configurations, the target shell/ice-layer refractive index and thickness are retrieved after finite iteration cycles by an iterative algorithm based on OPD and ray deflection (IAORD). Experiments show that a relative error below ±2.1% is achieved for the target shell refractive index and thickness measurement, which is consistent with the simulated values of 2.19% for the refractive index and 1.09% for the thickness obtained from the test uncertainty analysis. The test uncertainty analysis also shows that the uncertainties of the ice-layer refractive index and thickness are 1.42% and 5.04% respectively. The measurement speed of the proposed system is 0.5 min for one target, which poses great potential on the in-situ measurement of the ICF target while minimizing environmental disturbance.